Personality Analysis of Jacob Black’s Character on Stephanie Meyer’s Novel “New moon” - Safnidar Siahaan; Selfrida Tampubolon (English Department, University of Riau Kepulauan, Batam,Indonesia, 2015)
This thesis discusses the novel by American author Stephanie Meyer entitled New Moon. This novel published by Little Brown and Company on September 2006 and this novel consists of 563 pages. This novel tells about the rarely love between human, vampire and ware wolf in Forks. This thesis focused on the Personality of Jacob Blacks influence his people around him especially his lover by his imprint as seen in New Moon Novel ByStephenie Meyer through Psychological approach. Meanwhile, too see Jacob’s character by personality theory as the main character of the novel, two question are formulated to guide or lead the analysis. Therefore there are two purposes of this research. First, to find out the characteristics of Jacob Black described in New moon novel by Stephanie Meyer. Finally, to know and explain Jacob’s personality by psychology approach.The method applied in this study is Qualitative research. The approach used in this study is psychology approach. The sources of data that are needed to support this study are taken from the novel new moon. Then the source contains the theories of literature, personality and another in terms of books and internet. Based on the result of the analysis, the answer to both questions is as follows. Firstly, Jacob Black’s characteristics are smart, brave, loving and friendly. Finally, Jacob’s characters influence his personality to save his lover and family and treaty from their enemy. Key Words: Character ,Personality